Classical solutions for D-branes in AdS - Parra Milián, S [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The main result of this dissertation is the study of the classical solutions for D-brane in Anti-de Sitter(AdS) space. They arised from the study of the orbit solution of the stablizer subgroup of a point on the boundary of the AdS space. To reach this goal we started making a brief summary of superstring theories, then we presented some geometric facts of the AdS space. A discussion of the effective low-energy action of a bosonic D-brane was done, then we wrote the action of a single D3-brane in the AdS5 space. Unfortunately, the study of this particular D-brane solution is not complete and goes beyond the scope of this dissertation. We intend to complete this work in the future, with this in mind a summary of the marginal deformation of N = 4 SYM ﬁeld theory and its gravity dual were given in the last chapter

No presente trabalho comprometemo-nos ao estudo de soluções clássicas para D-branas no espaço de Anti-de Sitter, as quais surgem da solução de órbita do subgrupo estabilizador de um ponto na fronteira no espaço AdS. Começamos por fazer uma breve revisão da teoria de supercordas e apresentamos algumas características da geometria do espaço AdS. Então fazemos uma discussão sobre a ação efetiva a baixas energias e, por último, escrevemos a ação de uma D3-brana no espaço AdS5. O estudo desta solução particular da D-brana não é completo e acaba por fugir ao escopo deste trabalho. Esperamos complementá-lo num futuro breve e, com isto em mente, concluímos a dissertação com um resumo de deformações marginais da teoria de campo N = 4 SYM e sua gravidade dual
Keywords: D-branas; Stabilizer subgroup; Teoria das supercordas